A novel heterogeneous wax deposit structure triggered by polyethylene vinyl acetate (EVA) wax inhibitors. Issue 13 (2nd November 2020) - Zhu, Haoran; Li, Chuanxian; Fan, Yuanbo; Guo, Peng; Yang, Fei; Sun, Guangyu; Yao, Bo; Xia, Zheng
Abstract: Polyethylene vinyl acetate (EVA) has been widely investigated and employed as polymeric wax inhibitor (PWI). In this paper, the wax deposition characteristics of synthetic oils with different concentrations of EVA PWI were investigated. The obtained surface and bottom wax deposits were analyzed through differential scanning calorimeter (DSC), polarizing microscope, Fourier transform-infrared spectroscopy (FT-IR) and high-temperature gas chromatography (HTGC). It is found that the EVA PWI could obviously decrease the wax deposition rate and accelerate the aging of wax deposits. Adding the EVA PWI can trigger a novel heterogeneous wax deposit structure, in which the wax appearance temperature and wax content increases continuously from the bottom to the surface layer. Compared to the bottom wax deposit, the surface wax deposit has higher concentrations of both EVA and high carbon number wax molecules (Cn > C25 ). The formation mechanism of the novel heterogeneous wax deposit structure was explained from two aspects. Firstly, the wax crystal morphology of surface layer is significantly changed from needlelike to diamond-like due to higher temperature and the accumulation of EVA and high carbon number wax molecules in the surface wax deposit, therefore, higher solid wax content is needed for the building of a continuous three-dimensional network structure to resist shearing of pipe flow. Secondly, the lower temperature and larger aspect ratio of wax crystals in the bottom wax deposit are adverse for the diffusion of wax molecules into the bottom wax deposit, thus the aging rate of bottom wax deposit is lower than that of surface layer. Graphical Abstract: uf0001